Potential production of bioplastics polyhydroxyalkanoates using residual glycerol - Albuquerque, Priscilla Barbosa Sales de; Araújo, Katarynna Santos de; Silva, Kelvin Augusto Azevedo da; Houllou, Laureen Michelle; Locatelli, Gabriel Olivo; Malafaia, Carolina Barbosa (Journal of Environmental Analysis and Progress, 2018)
Cupriavidus necator was used for polyhydroxyalkanoate (PHA) production with the aim to compare the substrate consumption between pure glycerol (PG) and the glycerol obtained from biodiesel industry (GB). Shake flask experiments were performed with 20 g/L for both the carbon sources, incubated in a shaking incubator at 35 ºC for up to 72 h. At the end, the residual carbon source was analyzed by HPLC, the biomass recuperation for biopolymer extraction and biopolymer characterized by FTIR. The results demonstrated that 35.75 % of PG was consumed during biomass production, while 45.08 % was the value consumed for GB, which can indicate the higher PHA accumulation in GB-sample, as observed by microscopy analyses. Fourier Transform Infrared (FTIR) spectroscopy was performed to confirm the PHA nature of PG and GB samples, and confirmed the establishment of more hydrogen bonds in the PG one, suggesting the surplus of glycerol in the obtained-biopolymer. Since it is interesting the utilization of GB for obtaining added-value products along with biodiesel, this study reported the efficient production of PHA by C. necator using GB as carbon source and its promising use in the bioplastic industry as an alternative product for petrochemical plastics, foreseeing the improvement of a sustainable industry based on biofuels and biopolymers.